2007
DOI: 10.3354/meps07009
|View full text |Cite
|
Sign up to set email alerts
|

Spatially referenced trap arrays detect sediment disposal impacts on lobsters and crabs in a New England estuary

Abstract: We employed spatially referenced trap arrays and side-scan sonar mapping of the sea floor to assess the impact of late autumn sediment disposal on local American lobster Homarus americanus and rock crab Cancer irroratus abundance in the neighborhood of a disposal site for harbor dredge spoils in Penobscot Bay, Maine, USA. The assumption that impacts on lobsters would be minimized if disposal were conducted in late autumn, when the commercial lobster fishery is at a seasonal low and lobsters are believed to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Integrating geo-referenced pots, hydroacoustic surveys and detailed habitat maps has been demonstrated as an effective and efficient method in a number of lobster studies [35] [37] . In this study, the combined benefits of pots and seafloor mapping have revealed significant and somewhat unexpected effects of habitat on lobster distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Integrating geo-referenced pots, hydroacoustic surveys and detailed habitat maps has been demonstrated as an effective and efficient method in a number of lobster studies [35] [37] . In this study, the combined benefits of pots and seafloor mapping have revealed significant and somewhat unexpected effects of habitat on lobster distribution.…”
Section: Discussionmentioning
confidence: 99%
“…competition, resource availability) mediators of movement ecology requires further study to understand how these dynamics can be expected to play out when these parameters are altered. Studies that integrate mark-recapture tagging of lobsters, such as Dunnington et al [ 12 ] and O’Donnell et al [ 42 ], with acoustic telemetry, similar to this work, would allow researchers to study more lobsters at a lower resolution while still gathering high resolution data from the acoustically tagged individuals. Mark-recapture studies also encourage increased engagement with fishers, as researchers rely on them to report captures of tagged lobster.…”
Section: Discussionmentioning
confidence: 91%